Effectiveness of helmets in preventing severe injuries in a setting with poorly enforced quality standards - Junaid Ahmad Bhatti (366799) (2015)
Helmets save lives, yet many countries do not have laws about their quality assessment or how they should be worn. We assessed the effectiveness of helmet use in preventing injuries in such a setting. The data were extracted from a large road traffic injury surveillance study in Karachi, Pakistan. We assessed the association of wearing helmets with several injury outcomes including deaths, injury severity (via New Injury Severity Score, NISS ≥ 9) and moderate or severe injury (via Abbreviated Injury Score, AIS ≥ 2) to head, face, or other regions of the body. The data about helmet use was available for about 109,210 riders injured between January 2007 and December 2013. Only 6% of riders wore helmets, whereas this proportion was less than one percent in pillion riders and women. The rates were also lower among those aged 18 years or younger (1%) and those aged 18 to 25 years (4%). About 2% of riders died; 34% had an injury to the head region, 30% to face, 1% to chest, 5% to abdominal, 46% to extremities, and 61% to external body regions. Likelihood of dying was low among helmet users (adjusted odds ratio [aOR] = 0.37, 95% confidence interval [CI] = 0.28 to 0.50). Helmets reduced the likelihood of moderate to severe injuries to the head (aOR = 0.68, 95% CI = 0.58 to 0.80) but not to the face region (aOR = 1.37, 95%CI = 1.17 to 1.62). Helmet users also had severer injuries in other body regions except for chest injuries. Helmets prevented deaths and severe head injuries but had limited effectiveness in preventing facial injuries in this setting with poor helmet use standards. More work is needed to understand the helmet wearing and rider behaviours in helmet users in this setting. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.21